Identification of patients with psychiatric disorders in a surgical unit: a prospective study of risk factors - Metta, Jayachandra Reddy; Chelamkuri, Mrudula (International Surgery Journal, 2019)
Background: Many a times, surgical patients suffer from both physical diseases and mental disorders. Psychiatric comorbidity has been reported to be very high (8-53%) in primary health care units in developing countries including India. Methods: This study was conducted among four hundred in-patients in the Department of General Surgery at Armed Forces Medical College, Pune from May 2015 to April 2016. Patients aged 18 and above were included. Patients who were too ill to participate and who did not consent were excluded. The presence or absence of psychiatric illness was assessed using the general health questionnaire (GHQ) 28 questionnaire. Results: The mean age of participants with psychiatric co-morbidities as diagnosed with GHQ 28 was 46.79±12.73 years. The prevalence of psychiatric co-morbidities was more amongst females (76.35%) when compared to males (63.09%) with a statistical significance (95% CI: 2.08-23.61; p<0.05). The prevalence of psychiatric co-morbidities was more amongst participants living in a nuclear family (89.87%) than in a joint family (36.19%) (95% CI: 40.05-65.24; p<0.001). 74.62 % of the participants with psychiatric comorbidities had medical comorbidities as well. Conclusions: There was high prevalence of psychiatric co-morbidities in the participants of this study. We found that more than 2/3rd patients had psychiatric co-morbidity according to GHQ-28 total score, of which most common was found to be somatoform disorders, followed by mixed anxiety and depressive disorders.